The Influence of Personality and Burnout on Turnover Intention with Employee Engagement as a Mediating Variable - Dea Rahmawati; Putri Okta Agianti; Kartono Kartono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study examines the influence of personality and burnout on turnover intention at PT Tunggal Indo Tbk, using employee engagement as a mediating variable. A total of 70 respondents filled out a questionnaire in order to collect data using a quantitative approach. The collected data was examined to test its validity and reliability to ensure accuracy and consistency. The data was analyzed using SmartPLS 4.0 and Partial Least Square (PLS). The study found that personality positively impacts employee engagement, which reduces turnover intention. Burnout dramatically reduced employee engagement and increased turnover intention. Employee engagement strongly affects personality, burnout, and turnover intention. The importance of human resource management in controlling personality and burnout to create a happy work environment can help organizations retain staff and boost productivity.